Rent A Genius - "Cross, Gillian" (Puffin Books: London, 1993)
Sophy's always giving good advice, but her family just aren't grateful. She decides not to waste time on them, and she puts up a poster - offering advice to people who'll pay for it. For fifty pence, she'll deal with any problem, from finding yellow tomatoes to sorting out a football team
Keywords: Children's stories- English fiction